10.1002/9781118797914 (CrossRef Listing of Deleted DOIs, 2000)
BACKGROUND: Guillain-Barré syndrome (GBS) is an acute immune-mediated peripheral neuropathy for which therapeutic apheresis is an established treatment option. Various treatment modalities, including double filtration plasmapheresis (DFPP), are widely used in clinical practice; however, real-world data on their clinical outcomes and adjunctive treatment strategies remain limited. METHODS: We retrospectively analyzed 43 patients with GBS treated at a single tertiary center between June 2018 and October 2024, including 36 patients who received DFPP-containing regimens and 7 who received IVIG alone. Short-term functional outcomes were assessed using the modified Rankin scale (mRS) and Hughes functional grading scale (HFGS) at hospital admission before treatment and after completion of inpatient treatment. Changes in immunoglobulin and complement levels were evaluated in patients receiving DFPP. Exploratory analyses compared functional score changes across different treatment regimens. RESULTS: At hospital discharge, mRS and HFGS scores were significantly lower than baseline in patients receiving DFPP alone, DFPP combined with intravenous methylprednisolone, or IVIG alone. No significant differences in changes in functional scores were observed between the DFPP-alone and IVIG-alone groups or between the DFPP-alone and DFPP-plus-corticosteroid groups. DFPP significantly reduced serum immunoglobulin and complement levels; however, the percentage reductions in IgG, IgA, and IgM were not significantly correlated with short-term changes in mRS or HFGS scores. CONCLUSION: In this real-world cohort, DFPP-containing treatment was associated with short-term improvement in functional scores from hospital admission to hospital discharge. No statistically significant difference in short-term functional improvement was detected between the DFPP-alone and DFPP-plus-IVMP groups. However, the small sample size, heterogeneous treatment regimens, and lack of long-term follow-up preclude conclusions regarding sustained or comparative efficacy.